The Quality of Public Services in Buniwangi Village Government, Cianjur District - aisah, ira ariani (GoResearch - Research & Publishing House, 2024)
This study aims to determine the extent to which the quality of public services implemented by the Buniwangi Village Government towards the local community. This research used a qualitative approach, with data collection techniques through in-depth interviews with the people of Buniwangi Village as the main informants. This method was chosen to obtain a more detailed and in-depth picture of the community's perceptions and experiences of the services provided. Based on the results of the research, it is known that in general the quality of public services implemented by the Buniwangi Village Government has been running quite well. This is reflected in the level of community satisfaction in several aspects of services such as population administration, social assistance, and village information services. However, there are still a number of obstacles, such as services that are not evenly distributed throughout the village area and less than optimal performance in certain service areas. Therefore, efforts are needed to improve and equalize the quality of services so that the entire community can benefit maximally from the public services that are organized.